Treatment of drill cuttings using microemulsion - Tereza Neuma de Castro Dantas; Daniel Nobre Nunes da Silva; Afonso Avelino Dantas Neto; Tycianne Janynne de Oliveira Cabral; Aécia Seleide Dantas dos Anjos (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Conventional treatment of drill cuttings, as drying and thermal desorption, is failing to meet environmental and economic standards; therefore, new alternatives for the treatment of this waste must be developed. The purpose of this study was to remove n-paraffin from drill cuttings using microemulsion systems (MES). The extraction percentage (%) of n-paraffin was quantified by gas chromatography with a flame ionization detector. The optimization of extraction parameters showed that the extraction percentage (%) is directly proportional to the stirring speed and contact time and inversely proportional to the HLB of the surfactant used in the microemulsion system. Results for MES using Alkonat® L90 and Renex® 95 were similar, but Alkonat® L90 was chosen as the best system considering the environmental issue. The MES/cuttings ratio did not influence the percentage of n-paraffin extracted, reaching 55.03% and 56.32% for the ratios of 0.5 and 2.0, respectively. The reuse of MES in multiple extractions showed that MES can be reused in up to two extractions, obtaining up to 86% extraction. The optimal parameters for Alkonat® L90 microemulsion systems were MES/cuttings ratio of 1.0, stirring speed of 132 strokes, and contact time of 80 min, achieving 86.27% extraction. Results obtained in this study may help to better understand n-paraffin removal from drill cuttings by MES, considering the future use of this technology in the design of an industrial treatment plant for both onshore and offshore operations.